Regorafenib plus best supportive care versus placebo plus best supportive care in Asian patients with previously treated metastatic colorectal cancer (CONCUR): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 6 (June 2015) - Li, Jin; Qin, Shukui; Xu, Ruihua; Yau, Thomas C C; Ma, Brigette; Pan, Hongming; Xu, Jianming; Bai, Yuxian; Chi, Yihebali; Wang, Liwei; Yeh, Kun-Huei; Bi, Feng; et al.
Summary: Background: In the international randomised phase 3 CORRECT trial (NCT01103323 ), regorafenib significantly improved overall survival versus placebo in patients with treatment-refractory metastatic colorectal cancer. Of the 760 patients in CORRECT, 111 were Asian (mostly Japanese). This phase 3 trial was done to assess regorafenib in a broader population of Asian patients with refractory metastatic colorectal cancer than was studied in CORRECT. Methods: In this randomised, double-blind, placebo-controlled, parallel-group, phase 3 trial done in 25 hospitals in mainland China, Hong Kong, South Korea, Taiwan, and Vietnam, we recruited Asian patients aged 18 years or older with progressive metastatic colorectal cancer who had received at least two previous treatment lines or were unable to tolerate standard treatments. Patients had to have an Eastern Cooperative Oncology Group performance status of 0 or 1, life expectancy of at least 3 months, and adequate bone marrow, liver, and renal function, without other uncontrolled medical disorders. We randomly allocated patients (2:1; with a computer-generated unicentric randomisation list [prepared by the study funder] and interactive voice response system; block size of six; stratified by metastatic site [single vs multiple organs] and time from diagnosis of metastatic disease [<18 months vs ≥18 months]) to receive oral regorafenib 160 mg once daily or placebo on days 1–21 of each 28 day cycle; patients in both groups were also to receive best supportive care. Participants, investigators, and the study funder were masked to treatment assignment. The primary endpoint was overall survival, and we analysed data on an intention-to-treat basis. This trial is registered withClinicalTrials.gov, numberNCT01584830 . Findings: Between April 29, 2012, and Feb 6, 2013, we screened 243 patients and randomly assigned 204 patients to receive either regorafenib (136 [67%]) or placebo (68 [33%]). After a median follow-up of 7·4 months (IQR 4·3–12·2), overall survival was significantly better with regorafenib than it was with placebo (hazard ratio 0·55, 95% CI 0·40–0·77, one-sided p=0·00016; median overall survival 8·8 months [95% CI 7·3–9·8] in the regorafenib group vs 6·3 months [4·8–7·6] in the placebo group). Drug-related adverse events occurred in 132 (97%) of 136 regorafenib recipients and 31 (46%) of 68 placebo recipients. The most frequent grade 3 or higher regorafenib-related adverse events were hand–foot skin reaction (22 [16%] of 136 patients in the regorafenib group vs none in the placebo group), hypertension (15 [11%] vs two [3%] of 68 patients in the placebo group), hyperbilirubinaemia (nine [7%] vs one [1%]), hypophosphataemia (nine [7%] vs none), alanine aminotransferase concentration increases (nine [7%] vs none), aspartate aminotransferase concentration increases (eight [6%] vs none), lipase concentration increases (six [4%] vs one [1%]), and maculopapular rash (six [4%] vs none). Drug-related serious adverse events occurred in 12 (9%) patients in the regorafenib group and three (4%) in the placebo group. Interpretation: This phase 3 trial is the second to show an overall survival benefit with regorafenib compared with placebo in patients with treatment-refractory metastatic colorectal cancer, substantiating the role of regorafenib as an important treatment option for patients whose disease has progressed after standard treatments. In this trial, preceding standard treatments did not necessarily include targeted treatments. Adverse events were generally consistent with the known safety profile of regorafenib in this setting. Funding: Bayer HealthCare Pharmaceuticals.